Why are we bad at picking good leaders : a better way to evaluate leadership potential - Cohn, Jeffrey, 1966-; Moran, Jay, 1968- (San Francisco : Jossey-Bass, 2011)
"Almost 80% of Americans believe that we are suffering from a crisis of leadership, but rather than asking, why are leaders failing, we need to ask, "Why aren't we choosing better leaders?" Ever wonder what goes on behind closed board room doors when organizations pick their top leaders? It can be a contentious, secretive, even brutal process. Most of our leaders look good on paper--they have charisma, credentials, and confidence--yet they lack the real qualities that are necessary to succeed. In Why Are We Bad at Picking Good Leaders?, Cohn and Moran share the same insights and ideas they use to help organizations make better choices. Revealing seven essential attributes of all great leaders, they offer a fresh and powerful evaluation technique anyone can use to assess leader potential. Through dynamic, first-hand accounts from the business world, entertainment, sports, politics, education, and philanthropy, the authors offer the ultimate insider access and reveal how top organizations find and choose the best talent. Offers multiple ways to evaluate leaders, and how these 7 leadership attributes combine to create the best (and worst) in leaders Features interviews with with Mike Krzyzewski, Coach, 2008 US Men's Olympic Basketball team, Jeff Bezos, CEO of Amazon; George Steinbrenner, Scott Davis, CEO of UPS; Peter Loscher, CEO of Siemens; Toby Cosgrove, CEO, Cleveland Clinic; Martha Ingram, Board Chair of Vanderbilt University and Ingram Industries; Hollywood movie directors, and many others Includes academic study and field training at institutions such as Harvard, Yale, INSEAD, and IMD for developing future leaders. Fresh and compelling, Why Are We Bad at Picking Good Leaders? shows how great leaders can be spotted and why they succeed - and is soon to the definitive resource guide for about choosing better leaders"--
Includes bibliographical references and index.
Keywords: Leadership; Leadership -- Case studies